Pengaruh Return On Assets Dan Return On Equity Terhadap Harga Saham Dengan Debt To Equity Ratio Sebagai Variabel Intervening Pada Perusahaan Manufaktur Sektor Consumer Cyclicals Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019 – 2023 - Yona, Desma; Lusiana, Lusiana; Saputra, Deni (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
This study aims to determine the effect of Return On Asset and Return On Equity on Stock Prices with Debt To Equity Ratio as an Intervening variable in consumer cyclicals manufacturing companies listed on the Indonesia Stock Exchange in 2019-2023. The population in this study used consumer cyclicals manufacturing companies listed on the Indonesia Stock Exchange in 2019-2023 with the Purpose Sampling method. The analysis method in this study is multiple linear regression analysis and path analysis. The results of this study determine that Return On Asset partially has a significant effect on Debt To Equity Ratio. Return On Equity partially has a significant effect on Debt To Equity Ratio. Return On Asset has a significant effect on Stock Price. Return On Equity partially does not have a significant effect on Stock Price. Debt To Equity Ratio partially does not have a significant effect on Stock Price. Debt To Equity Ratio has not been able to moderate the relationship between Return On Asset and Stock Price. Debt To Equity Ratio is able to moderate the relationship between Return On Equity and Stock Price in consumer cyclicals manufacturing companies listed on the Indonesia Stock Exchange in 2019-2023.